The Influence of the AIR (Auditor Intellectually Repetition) Model on Middle School Students' Interest in Learning Islamic Religious Education - Rizka Mirda Aulia; Erlina; Sunarto (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
The low interest of students in learning Islamic Religious Education (PAI), especially in the indicator of